2018
DOI: 10.1083/jcb.201801122
|View full text |Cite
|
Sign up to set email alerts
|

EHD2 is a mechanotransducer connecting caveolae dynamics with gene transcription

Abstract: Caveolae are small invaginated pits that function as dynamic mechanosensors to buffer tension variations at the plasma membrane. Here we show that under mechanical stress, the EHD2 ATPase is rapidly released from caveolae, SUMOylated, and translocated to the nucleus, where it regulates the transcription of several genes including those coding for caveolae constituents. We also found that EHD2 is required to maintain the caveolae reservoir at the plasma membrane during the variations of membrane tension induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 42 publications
5
58
0
Order By: Relevance
“…A number of functions have been ascribed to caveolae. A quite recent one is their ability to protect cells against mechanical stress by stretching of the PM, which provides an explanation of the very high density of caveolae in some cell types, such as skeletal muscle, endothelial cells and adipocytes [12,[63][64][65][66][67][68]. Other functions include fatty acid [69] and Ca 2+ [70] transport, as well as endocytosis as discussed below.…”
Section: Caveolaementioning
confidence: 99%
See 1 more Smart Citation
“…A number of functions have been ascribed to caveolae. A quite recent one is their ability to protect cells against mechanical stress by stretching of the PM, which provides an explanation of the very high density of caveolae in some cell types, such as skeletal muscle, endothelial cells and adipocytes [12,[63][64][65][66][67][68]. Other functions include fatty acid [69] and Ca 2+ [70] transport, as well as endocytosis as discussed below.…”
Section: Caveolaementioning
confidence: 99%
“…In 2012, two groups published that the protein EHD2 (an ATPase) had a stabilizing function at caveolae, preventing pinching off of these structures from the plasma membrane [61,62]. More recently, it was reported that EHD2 is rapidly released from caveolae under mechanical stress, SUMOylated, and translocated to the nucleus, where it regulates the transcription of several genes including those coding for caveolae constituents [63].…”
Section: Caveolaementioning
confidence: 99%
“…Caveolae are small membrane invaginations of the plasma membrane that are abundantly found 49 in adipocytes, endothelial and muscle cells (Cheng and Nichols, 2016). They have been implicated in the 50 regulation of membrane tension (Sinha et al, 2011;Torrino et al, 2018) Loss of Cav1/Cav3 or Cavin1 results in a complete lack of caveolae from the plasma membrane 61 (Drab et al, 2001;Hill et al, 2008;Liu et al, 2008). Also, Cavin2 knockout (KO) mice show a decreased 62 number of caveolae at the plasma membrane in adipocytes and lung endothelium, but not in 63 cardiomyocytes or heart endothelium, suggesting a cell-type specific function (Hansen et al, 2013).…”
Section: Introduction 48mentioning
confidence: 99%
“…During this process, the Cav/cavin1 interaction is weakened and cavin1 is released into the cytosol, while free Cavs increase at the plasma membrane and EHD2 enters the nucleus. 54,55 When returned to isoosmotic conditions, caveolae reassemble at the cell surface.…”
Section: Syt11 Positively Regulates Caveolar Response Upon Hypoosmomentioning
confidence: 99%